Evolution of agricultural cooperatives in Romania in 2014 - Florentin Bercu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
This paper analyses the recent evolution of Romanian modern agricultural cooperatives. The purpose is to present a synthesis of the current study to have a real starting point and lay the foundations according to which appropriate measures may be taken for the organisation of food producers into agricultural cooperatives and for making efficient the Romanian food sector. Although in our country, there is still a reticence about the cooperatives due to the history, especially among those who are over 45 years old the mentality of farmers has started to change, becoming aware of the importance of association. In the agricultural cooperatives in Romania, there have been considerable evolutions in comparison with the financial years 2011 and 2012. The number of agricultural cooperatives has increased in only one year by 26%, the turnover has increased by 59%, reaching lei 292,092,239, and the number of employees has increased by 50%. Unfortunately, in the top of Romanian agricultural cooperatives, there are only agricultural cooperatives and cooperative companies which carry out input purchase and obtained raw material sale services (cereals, industrial crops, livestock, etc.) by the members, unlike the Occidental ones where the collection/storage/processing and common marketing services are predominant due to which they obtain high value added products. The small and average producers in the Romanian food sector must understand that without a reform aiming at making efficient the professional organisations with economic purpose and their merger into efficient agricultural cooperatives, our agriculture shall continue to live from its past glory.
Keywords: 330; agricultural cooperatives; Romanian agricultural sector; agricultural policies; evolution